Can accident and emergency nurse practitioners interpret radiographs? A multicentre study. Issue 2 (March 1998) - Meek, S; Kendall, J; Porter, J; Freij, R
Abstract : OBJECTIVE: To assess the ability of nurse practitioners in accident and emergency (A&E) to interpret distal limb radiographs, by comparison with senior house officers. DESIGN: Nurse practitioners and senior house officers in 13 A&E departments or minor injury units were shown 20 radiographs of distal limbs, with brief history and examination findings, and asked to record their interpretation. OUTCOME MEASURE: A total score for each subject was calculated by comparing answers against agreed correct responses. RESULTS: Nurse practitioners in general compared favourably with senior house officers. Those nurse practitioners who interpret radiographs as part of their role in minor injury units performed as well as the experienced senior house officer group. CONCLUSIONS: Nurse practitioners in A&E are able to interpret radiographs to a standard equal to senior house officers with three to five months' experience. Those nurse practitioners actively interpreting radiographs as part of their role in minor injury units are able to interpret radiographs to the same standard as senior house officers with more than five months' experience.